Cutaneous manifestations of disseminated Penicillium marneffei mycosis in five HIV-infected patients - Chiewchanvit S. (2014)
Five cases of disseminated Penicillium marneffei mycosis of Thai HIV patients, presented between November 1990 and April 1991, have been investigated. All patients were male and had bone marrow involvement. They showed mucocutaneous lesions with papules predominantly on the faces and upper extremities (5 cases), palatal papules (3 cases), and chronic genital ulcer (2 cases). P. marneffei was cultured, and the specific tissue form of the fungus was demonstrated histopathologically from skin and bone marrow specimens. In future, with increasing awareness of mucocutaneous lesions, disseminated penicilliosis in HIV-infected patients might be diagnosed sooner, thus leading to earlier therapy and better prognosis of the disease.